13, 14-Dihydrocoptisine – The genuine alkaloid from Chelidonium majus. (March 2015) - Paulsen, Jana; Yahyazadeh, Mahdi; Hänsel, Sophie; Kleinwächter, Maik; Ibrom, Kerstin; Selmar, Dirk
Graphical abstract: The genuine main alkaloid of greater celandine ( Chelidonium majus ) is 13, 14-dihydrocoptisine and not coptisine as reported earlier. Structure was elucidated by one- and two-dimensional NMR techniques. In vivo, after tissue injuries, dihydrocoptisine is oxidized and converted to coptisine. Highlights: The genuine main alkaloid of Chelidonium majus is 13, 14-dihydrocoptisine. It is not coptisine as reported earlier. Dihydrocoptisine was isolated from leaves of greater celandine. Structure was elucidated by one- and two-dimensional NMR techniques. After tissue injuries, dihydrocoptisine is oxidized and converted to coptisine. Abstract: The genuine major benzylisoquinoline alkaloid occurring in the traditional medicinal plant greater celandine ( Chelidonium majus L.) is 13, 14-dihydrocoptisine and not – as described previously – coptisine. Structure of 13, 14-dihydrocoptisine was elucidated. The discrepancy between the alkaloid pattern of the living plants and that of detached and dried leaves is due to the rapid and prompt conversion of 13, 14-dihydrocoptisine to coptisine in the course of tissue injuries. Indeed, apart from the major alkaloid, some minor alkaloids might also be converted; this however is not in the centre of focus of this paper. This conversion is initiated by the change of pH. In vivo 13, 14-dihydrocoptisine is localized in the acidic vacuoles, where it is stable. In contrast, in the neutral milieu, which results when vacuoles are destroyed in the course of tissue injuries, the genuine alkaloid is oxidized to yield coptisine. Accordingly, when alkaloids from C. majus should be analyzed, any postmortal conversion of 13, 14-dihydrocoptisine has to be prevented.